2018
DOI: 10.1177/0361198118776159
|View full text |Cite
|
Sign up to set email alerts
|

How Roundabout Entry Design Parameters Influence Safety

Abstract: Roundabouts are considered the safest intersection design; however, the safety effect may not be satisfactory at each specific roundabout. This is true especially in countries where roundabout design is a relatively new concept, such as in the Czech Republic. Specifically, most Czech roundabout crashes were found to occur on entries. This motivated the presented study to investigate how entry design parameters influence safety on Czech roundabouts and, if possible, use the findings to update current Czech roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…According to their findings, the frequency of crashes tended to rise with increase in the traffic volume and inscribed circle diameter. Novák et al (2018) found that entry design parameters significantly influence safety in terms of crash frequency and speeds at the roundabout, especially at the approach level. Similarly, Al-Marafi et al (2020) considered traffic and geometric features and their influences on the safety performance of roundabouts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to their findings, the frequency of crashes tended to rise with increase in the traffic volume and inscribed circle diameter. Novák et al (2018) found that entry design parameters significantly influence safety in terms of crash frequency and speeds at the roundabout, especially at the approach level. Similarly, Al-Marafi et al (2020) considered traffic and geometric features and their influences on the safety performance of roundabouts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crash prediction models were used by various researchers to explain the safety aspects at various levels based on the influence of geometric and traffic characteristics (6,15,(25)(26)(27)(28)(29)(30)(31)(32). The variables considered are radius at entry, the width of entry, angle to next leg, central island diameter, entry path radius, average annual daily traffic, number of approaches, and circulating lane number.…”
Section: Crash Prediction Modelsmentioning
confidence: 99%
“…Furthermore, the crash frequency of segments can be predicted by using various regression methods such as negative binomial ( 20 ), multiple logistic ( 21 ), and zero-inflated negative binomial ( 22 ). In addition to this, some researchers ( 6 , 2326 ) have suggested that Poisson and negative binomial models can be a better model for predicting the discrete, rare, and non-negative crash count. Though the above models are widely used for modeling the crash count at various transportation facilities, there are limited studies that modeled roundabouts safety using these models.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Ulusal ve uluslararası trafik kaza kayıtlarına bakıldığında kavşak noktalarının potansiyel risk taşıdığı görülmektedir. Yapılmış olan istatiksel çalışmalar Amerika Birleşik Devletleri'nde ölümlü ve yaralanmalı kazaların %50'sinden fazlasının, Avrupa ülkelerinde ise trafik kazalarının ortalama %27'si ve ölümlü kazaların ortalama %10'unun kavşaklarda meydana geldiğini göstermektedir [5][6][7]. Ülkemiz karayolu ulaşım ağında ölümle, yaralanmayla veya maddi hasarla sonuçlanan trafik kazalarına ait veriler incelendiğinde, kazaların %50'sinin şehir içi, %30'unun ise şehirlerarası kavşaklarda meydana geldiği görülmektedir [8].…”
Section: Gi̇ri̇ş (Introduction)unclassified